Review on the ammonia-blend as an alternative fuel for micro gas turbine power generation - Mohammed A.G.; Mansyur N.; Hasini H.; Elfeky K.E.; Wang Q.; Ali M.H.; Om N.I. (Elsevier Ltd, 2025)
To achieve zero carbon emissions, replacing conventional fuels in combustion engines and gas turbines with carbon-free fuel is of utmost important. While hydrogen is effective in mitigating climate change, the cost challenges in liquefaction and transportation persist. Ammonia (NH3), a carbon-free fuel with its higher volumetric energy density and cost advantages, emerges as a potential substitute. This review reports the most recent studies on NH3 as a fuel for micro gas turbine (MGT), highlighting both advantages and limitations. The performance and emissions in gas turbines are discussed. The main obstacles to a widespread usage of NH3 blends as fuel for MGT power generation are addressed, along with the current stage of commercialization. The review explores all the numerical and experimental works on NH3 blend in combustion system of MGT, and further presents ways to overcome the limitations associated with the combustion, such as high NOx emissions and low burning velocity. ? 2024 Hydrogen Energy Publications LLC